STUDI ETNOBOTANI TUMBUHAN OBAT OLEH ETNIS SUKU DAYAK DI DESA KAYU TANAM KECAMATAN MANDOR KABUPATEN LANDAK - mila, Efre; Wardenaar, Evy; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2015)
West Borneo is very famous for the tropical rain forest that many various types of plant species.  Plant species used by very diverse societies, such as the plant underground layers, liana, terna, shrubs, and   the other tree species variety.  In line with the level of public awareness will be health care, use of medications derived from plants or treatment in the traditional way more popular.  Remember which can cure diseases and to work with more secure and economical, then constantly socialized to the community so that embedded a culture of using medicinal plants as options that align with medical treatment. The purpose of this research is to know the types of medicinal plants and its utilization by the villagers of timber cropping, knowing the benefits of medicinal plants and parts used and how to make it.  This research uses the technique of deskriftip with interviews and identification in the field, which is a descriptive addressed to people who know and recognize the utilization of medicinal plants, namely the respondent elected, among others, the village shaman/bahtra.  Based on the results of research on medicinal plants and its utilization around the village of timber Cropping sub Regency Landak, Foreman found 50 plant species grouped in 32 drug family.  Based on habitusnya, level a lot more herbs used as medicinal plants that is as much as 21 species (42%), based on the used section leaves a lot be utilized that is as much as 15 species (30%), based on how to use, how to drink a lot more use IE as much as 31 species (62%) based on the way of processing, boiling is used which is as much as 21 species (42%) and the form of the herb which is the most widely used is a form of single herb 49 species (98 percent).  In an effort to maintain and preserve knowledge society, need to be encouraged the cultivation of different kinds of plants that are utilized by the community and the need to do more research about the research contents of chemical types were found. Keyword : Dayak tribe, Kayu Tanam Village, medical plant.